2013
DOI: 10.1108/ss-09-2012-0028
|View full text |Cite
|
Sign up to set email alerts
|

Renovation status and technical condition of Norwegian dwellings

Abstract: Purpose -The purpose of this paper is to gain knowledge on the renovation status for Norwegian dwellings that can be used to design attractive energy efficiency measures. Norwegian dwellings are exposed to a windy, cold and moist climate and the technical condition of existing dwellings depend on the owners priorities regarding maintenance and renovation. The paper focuses on the renovation status and technical condition of privately owned detached houses built in Norway in the 1980s constituting 10 per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Lourenço et al (2006) presented the need to renovate the roof or facade due to water seepage and condensation in buildings from historical city centres in Portugal. In Norway (Risholt et al, 2013), the foundation was also one of the most defective building elements, but wet rooms and windows replaced the roof and exterior wall in acute need for renovation. In Finland serious damage from moisture has been found in 82 % of detached houses (mainly wooden) built since the 1950s, concentrated to wet areas, base floor structures and the joints between the base floor and wall structures (Heikkilä, 2005).…”
Section: Studied Houses and The Main Vulnerable Structuresmentioning
confidence: 99%
“…Lourenço et al (2006) presented the need to renovate the roof or facade due to water seepage and condensation in buildings from historical city centres in Portugal. In Norway (Risholt et al, 2013), the foundation was also one of the most defective building elements, but wet rooms and windows replaced the roof and exterior wall in acute need for renovation. In Finland serious damage from moisture has been found in 82 % of detached houses (mainly wooden) built since the 1950s, concentrated to wet areas, base floor structures and the joints between the base floor and wall structures (Heikkilä, 2005).…”
Section: Studied Houses and The Main Vulnerable Structuresmentioning
confidence: 99%
“…Eggers and Moumen (2013) found that between 1985 and 2009, 5 to 9 percent of the occupied units had moderate to severe physical problems, and some quality deficiencies existed in 43 to 56 percent of all units. Risholt et al (2013) noted that moisture-related defects in basements, bathrooms, and laundry rooms were most frequently observed in Norwegian dwellings; also, there were window and roof defects. The structural aspect of the home environment was associated with about 38 percent of all the home injuries in the owner-occupied housing stock repair program in New Zealand (Keall et al , 2013).…”
Section: Background Of Studymentioning
confidence: 99%